2016
DOI: 10.1021/acs.energyfuels.6b00699
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Reaction Confinement Effects on Coke Yield in Coal Pyrolysis

Abstract: The pyrolysis of agglomerating coal was analyzed by thermogravimetric analysis (TGA) coupled to microgas chromatography (μGC) to determine the effects of reactor confinement on solid product yield, tar evolution, and gas composition. The primary volatile products generated from pyrolysis are studied using two TGA crucibles with height to width aspect ratios of 0.11:1.0 and 2.0:1.0 for heating rates of 1, 3, and 10 K min −1 . Mass balances were determined from measurements of the solid residual, gaseous flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Subsequently, some aliphatic chains and aromatic rings are broken down to form hydrogen and small molecular alkanes, accompanied by highly active hydrogen and atomic free radical fragments. Finally, the pyrolysis reaction gradually decelerates, and the polycondensation reaction occurs to form tar and semicoke. , Examining Figure , HLH shows the lowest initial thermal decomposition temperature, whereas TX shows the highest. In the environmental stabilization stage, the weight of the sample is essentially stable, suggesting that the pyrolysis reaction of coal is completed.…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, some aliphatic chains and aromatic rings are broken down to form hydrogen and small molecular alkanes, accompanied by highly active hydrogen and atomic free radical fragments. Finally, the pyrolysis reaction gradually decelerates, and the polycondensation reaction occurs to form tar and semicoke. , Examining Figure , HLH shows the lowest initial thermal decomposition temperature, whereas TX shows the highest. In the environmental stabilization stage, the weight of the sample is essentially stable, suggesting that the pyrolysis reaction of coal is completed.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Finally, the pyrolysis reaction gradually decelerates, and the polycondensation reaction occurs to form tar and semicoke. 24,25 Examining Figure 3, HLH shows the lowest initial thermal decomposition temperature, whereas TX shows the highest. In the environmental stabilization stage, the weight of the sample is essentially stable, suggesting that the pyrolysis reaction of coal is completed.…”
Section: Methodsmentioning
confidence: 96%
“…The experimental setup was described in detail in previous works. 19,20 The hot volatile pyrolysis products were transferred via a 1 / 4 in. passivated stainless-steel tube heated to 275 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It has recently been shown via thermogravimetry and high-frequency gas chromatography that the residence time of pyrolysis tar in the solid−gas interface of the reacting solid can be systematically altered by changing the height and cross-sectional area of the reaction confinement. 19 It was demonstrated that increasing the residence times of tar within the solid−gas interface will increase tar cracking, leading to more hydrogen, methane, and solid carbon and decreasing tar production by 2.1−2.5 wt %. 19 The present work shows a set of experiments investigating the secondary tar cracking reactions in high-temperature pyrolysis environments by analyzing the change in tar composition as a result of the extended residence time.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation